Deep Talent : how to transform your organization and empower your employees through AI - Garg, Ashutosh 1976-; Garg, Ashutosh, 1956-; Ahluwalia, Kamal (New York : Kogan Page Inc, 2023)
"What's the secret to finding the right person for the job? And how do you ensure your existing employees thrive and flourish in the workplace? Deep Talent answers these questions and more, as it demonstrates how AI platforms can help you positively transform your business.Every successful business relies upon an effective workplace culture with employees that are driven, productive and knowledgeable. So it's vital that leaders do everything they can to hire, retain and train the people who are driving their growth. Deep Talent provides strategies and approaches that any business leader can adopt to reinvigorate their workforce. It highlights the rising significance of talent intelligence platforms which, when combined with human instinct, can streamline and enhance business practices.The recent transformation in workplace culture presents a huge opportunity for ambitious business leaders who want to positively transform their workplace culture and get ahead of the competition. Drawing upon fascinating case studies and first-hand research, Deep Talent provides clear strategies for supporting your workforce and using AI to its full potential. Uncover the cutting-edge ways in which you can reinvigorate the enthusiasm and productivity of your workforce and attract the best talent to your organization"--
Includes bibliographical references and index.
Keywords: Organizational change; Artificial intelligence; Personnel management; Success in business